Maslow's Theory on Building Character Education Through Children's Literature - Sakhi Herwiana (Peneliti.net, 2022)
Emerging technology brings both negative and positive impacts. The negative foreign culture and moral values will bring destruction to the young generation. Therefore, it is necessary to strengthen character education in children so that unfiltered negative culture can be avoided as early as possible. The purpose of this paper is to give insight and suggestions to the teachers to apply Maslow’s theory with literary works to instill character education in elementary school. This paper provides practical examples that can be applied in the school environment. Maslow’s theory is the most ideal learning theory. Literary works provide many examples of good character education that can be imitated. Meanwhile, Maslow’s theory prioritizes humanist education, where students must be treated as whole humans, not only in cognitive aspects but must involve emotional and social aspects. Strengthening character education through literary works has been widely carried out because literature has stories and characters that can be imitated, but no literature uses Maslow's theory. Literary works and Maslow's theory can be combined because they both have the same goal to shape the child's personality not only from an academic point of view but also from a non-academic perspective.